Effects of molecular structure of polycarboxylate superplasticizers on their dispersion and adsorption behavior in cement paste with two kinds of stone powder. (10th May 2018) - Feng, Hui; Pan, Lisha; Zheng, Qiang; Li, Jiacheng; Xu, Nai; Pang, Sujuan
Graphical abstract: Highlights: PCEs were adsorbed strongly by intercalation in muscovite. PCE and stone powder (SP) intercalation reduces the dispersion of cement-SP paste. PCE with short side chains has good SP tolerance. Abstract: Waste stone powder (SP) from machine-made sand, which can be substituted for natural sands in concrete causes environmental problems. To investigate effects of polycarboxylate superplasticizers (PCEs) molecular structure on their behavior in cement-SP paste, grain composition, mineral compositions, and zeta potentials of two kinds of SPs were measured. Effects of PCEs on their dispersion and adsorption behavior in cement-SP paste were investigated. The results show that the intercalation of SPs with PCEs caused PCE adsorption in the interlayer of SPs and decreased cement-SPs paste fluidity. The intercalation of PCE with Ledong stone powder (LDSP) was higher than with Haikou stone powder (HKSP), because that the intercalation between PCE and muscovite, which is present in LDSP and isn't present in HKSP is stronger than the other mineral composites. PCE-S1 has a short side chain which is difficult to be intercalated in SPs, caused higher cement-SP paste fluidity, and lower difference in adsorption amount between cement and SPs than the other PCEs. Thus, a short-side-chain-PCE has good SP tolerance.